ProBIZ: multimedia e-learning for SPM student using Gagne's Nine Events of instruction / Azizir Razi Ruhaizam - Ruhaizam, Azizir Razi (2025)
The ProBIZ e-learning platform aims to revolutionize the educational experience for students and teachers engaging with SPM Business subjects. This project leverages the ADDIE model and Gagne's Nine Events of Instruction to create an interactive, multimedia-rich learning environment. The platform integrates text, images, videos, animations, and interactive activities to enhance user engagement and content retention, encompassing planning, requirement analysis, design, implementation, development, testing, and documentation phases. The testing process evaluated the platform's usability, functionality, and instructional effectiveness. It included two primary constructs: user evaluation and expert evaluation. For user evaluation, 30 students from Form 4 at SMK Kota Masai (SKOMAS) participated, providing insights into the platform's engagement, ease of use, and learning outcomes. Expert evaluation involved three professionals with over three years of experience in multimedia and elearning development, focusing on functionality, content accuracy, and design quality. The results highlighted user satisfaction and significant improvements in student comprehension and retention of business concepts. Multimedia components received the highest score of 7.0, indicating their effectiveness in enhancing interactive learning experiences. Experts validated the platform's adherence to instructional design principles and suggested minor refinements to optimize its effectiveness. The ProBIZ courseware offers a dynamic and effective educational tool, aligned with contemporary instructional theories to support active learning and continuous improvement.